PHACE syndrome: Infantile hemangiomas associated with multiple congenital anomalies: Clues to the cause. Issue 4 (22nd December 2018) - Siegel, Dawn H.
Abstract : Infantile hemangiomas (IH) are the most common vascular tumor of infancy with an estimated 80, 000 annual diagnoses in the United States. The genetic mechanisms underlying IH and the related multi‐organ birth defect syndromes, PHACE (an acronym for P osterior fossa brain malformations, segmental facial H emangiomas, A rterial anomalies, C ardiac defects, E ye anomalies, and sternal clefting or supraumbilical raphe) and LUMBAR (an acronym for L ower body hemangiomas, U rogenital anomalies, M yelopathy, B one deformities, A norectal malformations/ A rterial anomalies, R enal anomalies) remain unsolved. With advances in next generation sequencing (NGS), genomic alterations have been identified in a wide range of vascular anomaly syndromes. We hypothesize that PHACE is a genetic disorder, caused by somatic mutations, likely in cancer genetic pathways. Identification of the genetic etiology will lead to improved diagnosis in PHACE syndrome and development of targeted therapies for IH and related congenital anomalies.